2004
DOI: 10.1186/bcr807
|View full text |Cite
|
Sign up to set email alerts
|

The DNMT3B C→T promoter polymorphism and risk of breast cancer in a British population: a case-control study

Abstract: Background Gene promoter methylation is an important regulator of expression and is a key epigenetic factor in tumorigenesis. DNA methylation is mediated by DNA methyltransferases (DNMTs), of which three active forms have been identified: DNMT1, DNM3A and DNMT3B. The C→T transition polymorphism (C46359T) in the promoter of the DNMT3B gene, which significantly increases transcriptional activity, has been postulated to increase the propensity for promoter-hypermethylation-mediated silencing of tumour suppressor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 18 publications
1
58
1
Order By: Relevance
“…In contrast, in a case-control study of 352 cases and 258 controls in a British population, it was found that the DNMT3B -149 C alleles had a nominally significant increased risk of breast cancer compared with TT homozygotes [12]. In a Japanese study of 152 gastric cancer patients and 247 controls, it was reported that only the T/T genotype was detected in all case and control subjects [27].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In contrast, in a case-control study of 352 cases and 258 controls in a British population, it was found that the DNMT3B -149 C alleles had a nominally significant increased risk of breast cancer compared with TT homozygotes [12]. In a Japanese study of 152 gastric cancer patients and 247 controls, it was reported that only the T/T genotype was detected in all case and control subjects [27].…”
Section: Discussionmentioning
confidence: 87%
“…Several case-control studies have been reported in which the association between the DNMT3B -149C>T polymorphism and risk of cancer was assessed [11][12][13][14]27,28]. However, the results from these molecular epidemiological studies are conflicting.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A genetic deficiency of DNMT3B causes a recessive human disorder characterized by immunodeficiency, centromere instability, and facial anomalies (32). In case-control studies, variants in other DNMTs (i.e., DNMT3L, DNMT1) have been associated with cancers (33)(34)(35)(36).…”
Section: Genetic Factors That Influence Dna Methylationmentioning
confidence: 99%
“…Genomewide association studies have shown that many susceptibility polymorphisms of genes are associated with breast cancer. Variants of DNMTs have been evaluated to determine relationships between DNMT polymorphisms and breast cancer risk (Montgomery et al, 2004;Cebrian et al, 2006;Ye et al, 2010;Xiang et al, 2010), but the results have been inconsistent. This study was performed to assess the association between single nucleotide polymorphisms (SNPs) in DNMTs and the risk for breast cancer among Han Chinese women from South China.…”
Section: Introductionmentioning
confidence: 99%